2023
DOI: 10.1007/s11255-023-03824-6
|View full text |Cite
|
Sign up to set email alerts
|

Does preoperative silodosin administration facilitate ureteral dilatation during flexible ureterorenoscopy? A randomized clinical trial

Tamer Diab,
Waleed El-Shaer,
Saad Ibrahim
et al.

Abstract: Purpose To assess whether preoperative administration of silodosin can facilitate the placement of ureteral access sheath (UAS) prior to flexible ureteroscopy (F-URS) and reduce the occurrence of ureteric injury in challenging cases. Methods This prospective randomized clinical trial was carried out on 147 patients diagnosed with upper ureteric stone or stone kidney, non-stented. The patients were randomly divided into two equal groups. Group A (silodosin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Recently, flexible-tip ureteral access sheath with suction was proved to increase the stone-free rate and decrease complications of FURS in treatment of renal calculi [ 15 ]. Diab et al showed the preoperative silodosin resulted in decreased incidence of ureteric injury during FURS [ 16 ]. Another study showed that the RIRS stone complexity score could predict stone-free status after FURS, but no scoring system could predict complications [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, flexible-tip ureteral access sheath with suction was proved to increase the stone-free rate and decrease complications of FURS in treatment of renal calculi [ 15 ]. Diab et al showed the preoperative silodosin resulted in decreased incidence of ureteric injury during FURS [ 16 ]. Another study showed that the RIRS stone complexity score could predict stone-free status after FURS, but no scoring system could predict complications [ 17 ].…”
Section: Discussionmentioning
confidence: 99%